The Implementasi Restorative Justice dalam Pembinaan ASN dan Masalah Akuntabilitas Keuangan Daerah - Syihab Syihabul Abror; Irsad Adriyanto (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Cenderawasih, 2026)
This research examines how the principles of Restorative Justice are applied in the guidance of civil servants (ASN) and in resolving financial accountability issues within the Regional Inspectorate of Demak Regency. Using a qualitative descriptive method, data were obtained through interviews, document reviews, and field observations. The study reveals that although Restorative Justice has notbeen formally institutionalized, its core values have been substantively embedded in internal supervisory practices. Elements of reparation, responsibility, and rehabilitation are evident in the financial recovery process, improvement of control systems, and ethical coaching for civil servants. This restorative model proves more effective than punitive measures in fostering ethical awareness, reinforcing integrity, and restoring public confidence. The findings suggest that Restorative Justice offers a fair, educational, and recovery-oriented alternative for ASN supervision while contributing to transparent, participatory, and integrity-based local financial governance.